Sharia Concept-Based Halal Tourism Development Strategy in Indonesia - Awaluddin, Awaluddin; Wira, Ahmad; Rawati, Mesis; Yusrial, Yusrial; Effendi, Yollanda (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
DSN-MUI Fatwa No. 108 of 2016 provides the legal framework for sharia tourism management in Indonesia, enabling tourism managers to enhance services and standards in managing tourist attractions and halal destinations. Tourism management falls under the Ministry of Tourism and Creative Economy, ensuring tourism aligns with sharia standards. However, challenges remain in implementing the fatwa as a reference for managing tourist attractions, with some elements applied before its issuance and others yet to be realized. This study examines the alignment between DSN-MUI Fatwa No. 108 of 2016 on sharia tourism and the 2019–2024 strategic plan for halal tourism development by the ministry. Using a qualitative descriptive method, it analyzes the alignment of the fatwa’s provisions with its implementation. The findings reveal that the 2019–2024 strategic plan includes developing halal tourism destinations by providing amenities and services that meet the needs of Muslim tourists, such as water for purification, halal food, prayer facilities, tour packages, and visitor guides. The plan also emphasizes broader halal tourism development and branding destinations as halal hubs. These principles align with the DSN-MUI fatwa’s guidelines for sharia-based tourism management, particularly regarding tourist destinations. Moreover, the vision, mission, and strategies in the strategic plan demonstrate synergy and editorial consistency with the fatwa’s provisions.